(untitled) (Research, Society and Development, 2020)
The article economically evaluates an initiative to native oyster (Crassostrea gasar) creation at floating tables in the municipality of Augusto Corrêa, Pará State. The production cost was evaluated by the methodology of the operational cost and economic efficiency indicators were adopted to estimate the profitability in five scenarios: 1) fattening a lot of seeds for two years, strategy adopted by the producer to commercialize all oysters in the medium size; 2, 3, 4 and 5) fattening a lot of seeds for one year, with 40%, 50%, 60% and 70% commercialization of the oysters in the medium size and the remainder for a 30% lower price. The mortality rate was standardized at 30% and the price of the dozen at the medium size at R 10.00. The implementation cost was estimated in R 21,494.00, the total operational cost per dozen calculated in R 7.94 for scenario 1 and R 4.86 for the other scenarios. Scenario 1 presented the least attractive economic efficiency indicators among all the scenarios. It is recommended a change in the production strategy in order to finalize the fattening of a lot of seeds in one year, in order to increase the profitability of the initiative.